PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA TATANAN RUMAH TANGGA MASYARAKAT DESA KARYA INDAH KECAMATAN BUNTULIA KABUPATEN POHUWATO - Solang, Margaretha; Saman, Widya Rahmawaty; Husain, Ilyas; Danial, Mohamad Ikbal Riski; Butungale, Said (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
Clean and healthy living behavior is an attitude or effort to train and empower the community so that they can always want to apply healthy living attitudes and be active in health movement activities. The purpose of the research is to find out how the implementation of clean and healthy living behavior in household settings in Karya indah Village, Buntulia District, Pohuwato Regency, Gorontalo Province through knowledge, observation and community culture. The research methods used are Socialization of Clean and Healthy Living Behavior (PHBS), Assistance and training on how to live a clean and healthy life without damaging the environment and Practice of clean and healthy living behavior of the Karya Indah Village community. The results of the research of the Karya Indah Village community are still lacking in the application of clean and healthy living behavior (PHBS), this is evidenced by the lack of awareness in maintaining a clean and healthy environment both in families, groups and communities. Lack of understanding of the importance of implementing clean and healthy living behavior (PHBS) by the people of Karya Indah Village.